Influenza Antiviral Prescribing for Outpatients With an Acute Respiratory Illness and at High Risk for Influenza-Associated Complications During 5 Influenza Seasons—United States, 2011–2016. (23rd October 2017) - Stewart, Rebekah J; Flannery, Brendan; Chung, Jessie R; Gaglani, Manjusha; Reis, Michael; Zimmerman, Richard K; Nowalk, Mary Patricia; Jackson, Lisa; Jackson, Michael L; Monto, Arnold S; Martin, Emily T; Belongia, Edward A; et al.
Abstract : During 5 influenza seasons, 37% of high-risk outpatients with influenza who presented early to care were prescribed antivirals. Early presentation and fever were associated with prescribing; 40% of high-risk outpatients with influenza presented early and 25% were afebrile. Abstract: Background: Influenza causes millions of illnesses annually; certain groups are at higher risk for complications. Early antiviral treatment can reduce the risk of complications and is recommended for outpatients at increased risk. We describe antiviral prescribing among high-risk outpatients for 5 influenza seasons and explore factors that may influence prescribing. Methods: We analyzed antiviral prescription and clinical data for high-risk outpatients aged ≥6 months with an acute respiratory illness (ARI) and enrolled in the US Influenza Vaccine Effectiveness Network during the 2011–2012 through 2015–2016 influenza seasons. We obtained clinical information from interviews and electronic medical records and tested all enrollees for influenza with real-time reverse-transcription polymerase chain reaction (rRT-PCR). We calculated the number of patients with ARI that must be treated to treat 1 patient with influenza. Results: Among high-risk outpatients with ARI who presented to care within 2 days of symptom onset (early), 15% (718/4861) were prescribed an antiviral medication, including 472 of 1292 (37%) of those with rRT-PCR–confirmed influenza. Forty percent of high-risk outpatients with influenza presented to care early. Earlier presentation was associated with antiviral treatment (odds ratio [OR], 4.1; 95% confidence interval [CI], 3.5–4.8), as was fever (OR, 3.2; 95% CI, 2.7–3.8), although 25% of high-risk outpatients with influenza were afebrile. Empiric treatment of 4 high-risk outpatients with ARI was needed to treat 1 patient with influenza. Conclusions: Influenza antiviral medications were infrequently prescribed for high-risk outpatients with ARI who would benefit most. Efforts to increase appropriate antiviral prescribing are needed to reduce influenza-associated complications.